Referensi Pemikiran Politik Nahdlatul Ulama (NU) - A. Bakir Ihsan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2009)
The growth of Islamic organization in Indonesian is difficult to release from politics. Although historically it was born as a cultural response, but in the presence, the development of organization is difficult to avoid “politics temptation”. This can be seen on Nahdlatul Ulama (NU) as one of the largest Islamic organizations in Indonesia. NU was not born from the political will, but rather as a response to socio-cultural development of society at that time. However, even though NU’s involvement in politics is not designed from birth, in fact NU able to play the phenomenal political role. This shows that NU inherently has a reference (thought) as the basis of the political practices. This paper will examine the political ideas of reference used by NU. One of them is thought of Imam Al-Mawardī especially in his monumental work, Al-Aḥkām Al-Sulthāniyyah which is a common reference of Sunni politics.